Empowerment of Islamic Religious Education Subject Teacher Consultative Groups on Students in Binjai City - Luthfia, Firza; Al Farabi, Mohammad (Universitas Muhammadiyah Ponorogo, 2024)
This study aims to analyse the empowerment efforts of the Islamic Religious Education Subject Teacher Consultation Group (MGMP PAI) in improving the competence and performance of teachers in teaching Islamic Religious Education subjects. The research method used is qualitative with the type of field research. Data were obtained through observation, interview, and document study. Data analysis was conducted using the Miles and Huberman technique consisting of data reduction, data presentation, and conclusion drawing. The results showed that the empowerment of MGMP PAI group has made a significant contribution in improving teachers' competence and performance. Through the MGMP forum, teachers have the opportunity to share experiences, provide mutual input, develop a curriculum that is relevant to students' needs, apply innovative learning methods, increase teachers' motivation and confidence in teaching, deepen students' understanding of Islamic values, improve students' learning experience, and support the achievement of PAI learning objectives.